Examination of physical properties of final product and drying properties of combined (convective pre-drying and freeze finish-drying) dehydration method - Antal, Tamás (Acta Agraria Debreceniensis, 2014)
In this study, the effects of freeze drying (FD), hot-air drying (HAD) and combined drying (HAD-FD) on drying characteristics, energy uptake, texture, rehydration and color of carrot were investigated. Results showed that HAD-FD significantly improved the drying time compared with FD under the same operating conditions, and the HAD-FD can reduce the total cost of dehydration. The drying kinetics was described by the Henderson-Pabis and the third degree polynomial models in the case of HAD, FD and HAD-FD. The HAD carrot samples were exhibited shrinkage, case hardening, poor rehydration and brown surface. The FD carrot cubes appeared porous structure, excellent rehydration, soft texture and loose color. The HAD-FD samples were superior to HAD products and was nearer in quality to FD products with respect to appearance, rehydration and surface resistance (texture). Finally, it is concluded that HAD-FD is effective in improving the FD drying rate. However, the combined drying has a small-scale adverse effect on product quality.